Could Less Be More When Assessing Patient-Rated Outcome in Spinal Stenosis?. Issue 10 (15th May 2015) - Mannion, Anne F.; Fekete, Tamas F.; Wertli, Maria M.; Mattle, Michele; Nauer, Selina; Kleinstück, Frank S.; Jeszenszky, Dezsö; Haschtmann, Daniel; Becker, Hans-Jürgen; Porchet, François
<x xml:space="preserve">Abstract</x> Study Design. Longitudinal study of the measurement properties of a brief outcome instrument. Objective. In patients undergoing surgery for lumbar spinal stenosis, we compared the responsiveness of the Core Outcome Measures Index (COMI) with that of the condition-specific Swiss Spinal Stenosis Measure (SSM), an instrument developed to assess patients with neurogenic claudication. Summary of Background Data. The COMI is a validated multidimensional questionnaire for assessing the key outcomes of importance to patients with back problems. Being brief, it is associated with minimal respondent burden and high completion rates. However, for a given pathology, intuitively it may be expected to be less responsive than a condition-specific instrument. Methods. A total of 91 patients (73 ± 8 yr; 53% males) completed the following questionnaires before surgery: COMI, SSM, Roland Morris Disability Questionnaire, back trouble "Feeling Thermometer, " pain numeric rating scale, EuroQoL-visual analogue scale. Twelve months postoperatively, 78/91 (86%) completed all the questionnaires again; they also rated the "global treatment outcome" (GTO; rated 1–5) and SSM "satisfaction with treatment result" (SSM-sat; rated 1–4), which were used as external criteria of treatment success. Results. Scores for the external criteria of success (GTO/SSM-sat) correlated with the change scores (baseline to 12 mo) in COMI (r = 0.57) and SSM (r = 0.54) to a similar extent. Using receiver operating characteristics, with GTO or SSM-sat dichotomized as external criterion, the area under the curve was similar for the COMI change score (0.86–0.90) and the SSM (sub)scales (0.80–0.90). Conclusion. With either SSM-sat or GTO serving as the external criterion, COMI was as responsive as the SSM. The COMI is well able to detect important change in lumbar spinal stenosis and has the added benefit of reducing the response burden for the patient and facilitating outcome comparisons with other spinal pathologies. Level of Evidence: 2